Question
upstudy study bank question image url

UBSTITUTION olve the equation given to find all real roots. \[ -z^{4}+6 z^{2}-35=-3 z^{4}-3 z^{2} \]

Ask by Sandoval Tran. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The real roots of the equation are \( z = -\frac{\sqrt{10}}{2} \) and \( z = \frac{\sqrt{10}}{2} \).

Solution

Solve the equation \( -z^{4}+6 z^{2}-35=-3 z^{4}-3 z^{2} \). Solve the equation by following steps: - step0: Solve for \(z\): \(-z^{4}+6z^{2}-35=-3z^{4}-3z^{2}\) - step1: Move the expression to the left side: \(-z^{4}+6z^{2}-35-\left(-3z^{4}-3z^{2}\right)=0\) - step2: Calculate: \(2z^{4}+9z^{2}-35=0\) - step3: Factor the expression: \(\left(z^{2}+7\right)\left(2z^{2}-5\right)=0\) - step4: Separate into possible cases: \(\begin{align}&z^{2}+7=0\\&2z^{2}-5=0\end{align}\) - step5: Solve the equation: \(\begin{align}&z \notin \mathbb{R}\\&z=\frac{\sqrt{10}}{2}\\&z=-\frac{\sqrt{10}}{2}\end{align}\) - step6: Find the union: \(\begin{align}&z=\frac{\sqrt{10}}{2}\\&z=-\frac{\sqrt{10}}{2}\end{align}\) - step7: Rewrite: \(z_{1}=-\frac{\sqrt{10}}{2},z_{2}=\frac{\sqrt{10}}{2}\) The real roots of the equation \(-z^{4}+6 z^{2}-35=-3 z^{4}-3 z^{2}\) are \(z_{1}=-\frac{\sqrt{10}}{2}\) and \(z_{2}=\frac{\sqrt{10}}{2}\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \(-z^{4}+6 z^{2}-35=-3 z^{4}-3 z^{2}\), first, let's simplify it. Bring all terms to one side: \[ -z^{4} + 6z^{2} - 35 + 3z^{4} + 3z^{2} = 0 \] This simplifies to: \[ 2z^{4} + 9z^{2} - 35 = 0 \] Next, let’s make a substitution to make it easier to solve. Let \(u = z^{2}\). The equation becomes: \[ 2u^{2} + 9u - 35 = 0 \] Now we can use the quadratic formula \(u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\): Here, \(a = 2\), \(b = 9\), and \(c = -35\). Calculating the discriminant: \[ D = b^{2} - 4ac = 9^{2} - 4 \cdot 2 \cdot (-35) = 81 + 280 = 361 \] Since \(D\) is positive, there are two real roots. Now calculating \(u\): \[ u = \frac{-9 \pm \sqrt{361}}{2 \cdot 2} = \frac{-9 \pm 19}{4} \] This gives us: 1. \(u = \frac{10}{4} = 2.5\) 2. \(u = \frac{-28}{4} = -7\) (not valid since \(u = z^2\) must be non-negative) Now substituting back \(u = z^2\): \[ z^{2} = 2.5 \implies z = \pm\sqrt{2.5} \] Thus, the real roots for \(z\) are: \[ z = \pm\frac{\sqrt{10}}{2} \] These are the solutions for the original equation.

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy